Niveles séricos de prolactina y uso de anticonceptivos hormonales en mujeres de edad fértil que acuden al Centro de Salud N° 1 de la ciudad de Loja. - Lucero Torres, Shirley Lilibeth (2017)
The prolactin is a glycoprotein hormone, secreted by the adenohypophysis, in charge of the development of the mammary glands and the production of milk during nursing; one of the rearons for the prolactin to rise, is the use of high doses of estrogens from which are composed the hormonal contraceptives that prevent pregnancy from occurring in women. The present research is of a descriptive type and of a transversal section named “Seric Levels of Prolactin and use of Hormonal Contraceptives in women of fertile age who attend the Health Center No. 1 of the city of Loja” during the period November 2016 and January 2017. Within the study, 80 women participated under their assent, which determined the seric levels of prolactin by the use of the Electrochemistry method, getting results that show from the total of women checked, a 30% of women in fertile stage that use hormonal contraceptives, maintain high levels of prolactin. A 76% of women in fertile age use combined injectable contraceptives. A 16% of women that use oral combined contraceptives and a 34%of women that use combined injectable contraceptives, have high levels of prolactin. From the total of women that use oral combined contraceptives the 79% present alterations such as headaches in a 36% and irregular menstrual cycles in a 36%. The total of women that use combined injectable contraceptives, present alterations especially headaches in a 31% and Irregular menstrual cycles in a 19% respectively. Keywords: prolactin, hormonal contraceptives, fertile stage, Electrochemistry